Membangun Web Konten Manajemen Sistem Secara Dinamis dengan Bahasa Pemrograman PHP Framework Codeigniter dengan Database Mariadb - Rio Bayu Sentosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The development of science at a time with rapid technological advancements to be applied in all fields. In addition to the creation of computers and the rapid development of the internet network today is also equipped with a web-base application that can be used to disseminate information quickly. The purpose of this study is that researchers want to build a Content Management System that aims specifically for the development of applications based on Rapid Application Development with the basic standard Application Portal News. Based on research that has been done and taking data samples at the Office of the Governor of West Sumatra by using the Action Research, library and laboratory research methods, it is known that the Content Management System that the researchers designed can be used as a news portal capable of disseminating information. Designing a Content Management System that uses the Codeigniter Framework, is able to provide convenience in developing the system in the future and can be used to build other website applications based on Rapid Application Development. Keywords: CMS, CodeIgniter, MariaDB, News Portal